Study of characteristics for simultaneous faults in distribution underground cable using DWT - Ngaopitakkul, A.; Pothisarn, C.; Leelajindakrairerk, M. (My University, 2011)
In the literature for fault detection, most of research works have never been mentioned about effects of simultaneous faults. This paper presents behavior of characteristics for simultaneous fault signals in an electrical distribution underground cable using wavelet transform. The fault signal is simulated using ATP/EMTP, and the behavior analysis of signals is performed using discrete wavelet transform (DWT). The DWT is used to detect the high frequency components. The results obtained from the analysis will be useful in the development of a detect fault scheme for electrical distribution underground cable in the future due to an effect of the other fault that occurs at the other side of the system; this leads to the malfunction of the protective relays. © 2011 IEEE.
Keywords: ATP/EMTP; discrete wavelet transform; simultaneous fault; Underground cable